2011
DOI: 10.3892/ijo.2011.1039
|View full text |Cite
|
Sign up to set email alerts
|

Pyrosequencing-based DNA methylation profiling of Fanconi anemia/BRCA pathway genes in laryngeal squamous cell carcinoma

Abstract: Abstract. Fanconi anemia (FA) associated genes [FANCA, -B, -C, FANCD1(BRCA2), -D2, -E, -F, -G, -I, -L, -M, FANCN (PALB2), FANCJ(BRIP1)and FA-linked BRCA1] encode proteins of DNA damage response pathways mutated in FA patients. FA is characterized by congenital malformations, chromosomal instability and high cancer susceptibility. FA patients have a 500-700 times higher risk of head and neck squamous cell carcinoma (HNSCC) compared to the non-FA population. As DNA methylation comprises one of the known gene ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 27 publications
0
23
0
1
Order By: Relevance
“…10 PCR products were mixed with binding buffer (Qiagen, Hilden, Germany) and sepharose coated with streptavidin (GE Healthcare, Chicago, USA), shaked for 10 min and cleaned on vacuum pump station in the following buffers: 70% EtOH, 0.2% NaOH, and washing buffer (Qiagen, Hilden, Germany). Single-strand amplicons were then mixed with annealing buffer (Qiagen, Hilden, Germany), the sequencing primer (0.4 µM), and then heated for 2 min at 85°C and cooled for primer hybridization.…”
Section: Pyrosequencingmentioning
confidence: 99%
“…10 PCR products were mixed with binding buffer (Qiagen, Hilden, Germany) and sepharose coated with streptavidin (GE Healthcare, Chicago, USA), shaked for 10 min and cleaned on vacuum pump station in the following buffers: 70% EtOH, 0.2% NaOH, and washing buffer (Qiagen, Hilden, Germany). Single-strand amplicons were then mixed with annealing buffer (Qiagen, Hilden, Germany), the sequencing primer (0.4 µM), and then heated for 2 min at 85°C and cooled for primer hybridization.…”
Section: Pyrosequencingmentioning
confidence: 99%
“…Somatic inactivation of the FA pathway by epigenetic silencing has been observed in several different types of sporadic cancer (Lyakhovich & Surralles, 2006), such as bladder cancer (Neveling et al, 2007), ovarian cancer (Lim et al, 2008), breast cancer (Wu, Shin-ya, & Brosh, 2008) cervical cancer (Narayan et al, 2004) and of course in HNSCC (Marsit et al, 2004;Szaumkessel et al, 2011 ;Wreesmann et al, 2007). Our own study has demonstrated the disruption of DNA methylation of promoter region in FANCA, BRCA1 and BRCA2 in squamous laryngeal carcinoma cell lines and primary tumors (Szaumkessel et al, 2011).…”
Section: Wwwintechopencommentioning
confidence: 91%
“…Our own study has demonstrated the disruption of DNA methylation of promoter region in FANCA, BRCA1 and BRCA2 in squamous laryngeal carcinoma cell lines and primary tumors (Szaumkessel et al, 2011). BRIP1 and FANCB have been shown to be higher and more frequently methylated compared to normal mucosa (Smith et al, 2010).…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Esta información fue concordante con el concepto de activación oncogénica mediada por hipometilación. A continuación analizamos el perfil de sobreexpresión de p73 y otros genes (BRCA1, HSP90, STAT1, FHIT, EGFR, p53, p16INK4a) asociados a activación por hipometilación [71][72][73][74][75][76][77][78][79] en microarreglos de tejidos (TMA, tissue microarray) de cáncer gástrico (mucosa gástrica tumoral y mucosa adyacente al tumor, n = 91) y gastritis (n = 148). En forma paralela a este análisis evaluamos las característi-cas histológicas de los casos según el sistema de Sydney para gastritis crónica y OLGA (Operative Link on Gastritis Assessment) para la evaluación de atrofia 80,81 .…”
Section: Hipometilación Del Adn Y Cáncer Gástricounclassified